Estimation of antibody titres in sheep immunized with capsular serogroup B Pasteurella multocida oil adjuvant vaccine (Bangladesh Journal of Infectious Diseases, 2024)
Background: Pneumonic pasteurellosis in sheep is an important economical disease in Bangladesh where Pasteurella multocida killed vaccine is prescribed as a preventive measure.Objective: The present research was conducted in 20 non-descript native sheep to estimate antibody titre in response to haemorrhagic septicaemia oil adjuvant vaccine by Pasteurella multocida Indirect Antibody Enzyme Linked Immunosorbent Assay.Methodology: This animal study was performed during January to March 2024 at Bangladesh Livestock Research Institute, Savar, Dhaka, Bangladesh. Twenty non-descript native female lamb born to non-immunized mother aged 3 to 4 months was acclimatized for on station experiment. The blood was collected at up to 63 days with seven days’ interval post vaccination. The vaccine seed molecularly identified for capsular sero-grouping by Polymerase Chain Reaction.Results: The seed bacterium was Pasteurella multocida capsular serotype B. The vaccine generated statistically significant (p